A comparative study between real-time PCR and loop-mediated isothermal amplification to detect carbapenemase and/or ESBL genes in Enterobacteriaceae directly from bronchoalveolar lavage fluid samples. (19th February 2020) - Vergara, A; Moreno-Morales, J; Roca, I; Pitart, C; Kostyanev, T; Rodriguez-Baño, J; Goossens, H; Marco, F; Vila, J
Abstract: Objectives: To evaluate and compare the efficacy of real-time PCR (Xpert Carba-R) and loop-mediated isothermal amplification (Eazyplex ® SuperBug CRE) for detecting carbapenemase carriage in Enterobacteriaceae directly from bronchoalveolar lavage (BAL). Methods: Negative BAL samples were spiked with 21 well-characterized carbapenemase-producing Enterobacteriaceae strains to a final concentration of 10 2 –10 4 cfu/mL. Xpert Carba-R (Cepheid, Sunnyvale, CA, USA), which detects five targets ( bla KPC, bla NDM, blaVIM, blaOXA-48 and bla IMP-1 ), and the Eazyplex ® SuperBug CRE system (Amplex-Diagnostics GmbH, Germany), which detects seven genes ( bla KPC, bla NDM, blaVIM, blaOXA-48, bla OXA-181, bla CTXM-1 and bla CTXM-9 ), were evaluated for the detection of these genes directly from BAL samples. Results: Xpert Carba-R showed 100% agreement with carbapenemase characterization by PCR and sequencing for all final bacteria concentrations. Eazyplex ® SuperBug CRE showed 100%, 80% and 27% agreement with PCR and sequencing when testing 10 4, 10 3 and 10 2 cfu/mL, respectively. False negative results for Eazyplex ® SuperBug CRE matched the highest cycle threshold values for Xpert Carba-R. Hands-on time for both assays was about 15 min, but Eazyplex ® SuperBug CRE results were available within 30 min, whereas Xpert Carba-R took around 50 min. Conclusions: We here describe the successful use of two commercial diagnostic tests, Xpert Carba-R and Eazyplex ® SuperBug CRE, to detect bacterial carbapenem resistance genes directly in lower respiratory tract samples. Our results could be used as proof-of-concept data for validation of these tests for this indication.